Web application for context-aware dietary recommendation & simple data analysis of stroke - Luo, Bingyi (Nanyang Technological University, 2020)
Why do we need to eat healthily? In short, healthy eating keeps the heart beating! Zero Hunger is not just about being full but eating right. The State of Food Security and Nutrition in the World (SOFI) 2019 report highlights that food insecurity is more than just hunger. Overweight and obesity are on the rise in almost all countries, contributing to 4 million deaths globally. The various forms of malnutrition are intertwined throughout the life cycle. A healthy diet is essential to maintain sound health, especially for people who are allergic to constitutions or have chronic diseases. Meanwhile, current technology is reshaping our daily lives significantly, and these applications make our lives more convenient. We hope through technology; we can help people understand what food is suitable for them and what food they should avoid controlling their allergies or chronic diseases. This project aims to help people on how to eat healthier and how to avoid eating wrong food by introducing a modern technology-based web application and gain the referenced food based on the analysis of the allergic or chronic diseases people may have. In this project, popular web application development frameworks are used to create a web application for this purpose. In the end, a fully functional web application is developed and deployed to provide people with the accessibility to all suggested food fit different people with allergic conditions and relevant analysis/knowledge and health logic.